Prevalence of complete childhood immunization and its associated factors among under-five children of military parents in military camp, Malacca - H., Noorhashirin; B., Anisah; M. Z., Nor Afiah (Community Health Society Malaysia, 2015)
Background: Immunization is one of the most important and cost effective public health interventions in preventing fatal infectious diseases among children worldwide. The prevalence of childhood immunization in the armed forces is lacking, not producible and not published in many international journals. The objective of this study was to determine the prevalence of childhood immunization under 5 years of age and its associated factors among military parents in Malacca. Materials and Methods: A cross sectional study was carried out among 276 military parents at a military camp in Malacca. Sampling was conducted using systematic random sampling from those who had fulfilled the criteria. A pre tested self-administered questionnaire was used to collect data on socio demographic factors, family factors, parents’ knowledge on immunization, parents’ perceptions towards health care providers and influences of external factors. Data was analyzed using SPSS version 21. Result: A total of 276 respondents were recruited for this study with a response rate of 86.3%. The mean age of the respondents was 30.2  4.6 years old. Majority of the respondents were female (97.1%), Malay (70.3%) and lived outside the military camp (94.2%). The median age for the children in the study was 24 months (IQR: 25). The prevalence of childhood immunization was 91.7% for complete immunization for age status. There was significant association between complete childhood immunization and parents’ knowledge and support from the spouse. The predictor for complete childhood immunization was high score of parents’ knowledge on childhood immunization (AOR= 16.63; 95% CI: 5.08, 54.45; P< 0.001). Conclusion: The prevalence of complete childhood immunization was high among parents in the Armed Forces. This study provides insights for future research, mainly on the influences of external factors and health care providers.